Significance of Trace Element Quantities in Benign and Malignant Giant Cell Tumors of Bone - Vladimir, Zaichick; Sofia, Zaichick (International Journal of Orthopedics and Rehabilitation, 2018)
To clarify the role of trace elements in the etiology and the pathogenesis of benign and malignant giant cell tumor (GCT) of bone, a nondestructive neutron activation analysis with high resolution spectrometry of long-lived radionuclides were performed. The silver (Ag), cobalt (Co), chromium (Cr), iron (Fe), mercury (Hg), rubidium (Rb), antimony (Sb), selenium (Se), and zinc (Zn) mass fraction were measured in three groups of samples: normal bone samples from 27 patients with intact bone (12 females and 15 males), who had died from various non bone related causes, mainly unexpectedly from trauma, and also in samples, obtained from open biopsies or after operation of 10 patients with benign GCT (4 females and 6 males) and 10 patients with malignant GCT (4 females and 6 males). The difference in the results between trace element contents in the three groups was evaluated by the parametric Student’s t-test and non-parametric Wilcoxon-Mann-Whitney U-test. In the bone affected by benign GCT the mean mass fractions of Ag, Co, Fe, Se, and Zn were significantly higher while the mean mass fraction of Rb was lower than in normal bone tissues. In malignant GCT tissue the mean mass fractions of Co, Fe, Sb, and Se were higher while the mean mass fraction of Rb was lower than in normal bone tissue. In malignant GCT tissue only the mean mass fractions of Fe and Rb were higher and the mean mass fractions of Ag and Zn were lower than in benign GCT tissue. Moreover, many correlations between trace elements found in the control group were no longer evident in the neoplastic bone. Thus, considerable changes in trace element content and their relationships were found in benign and malignant GCT and possible causes and effects of these alterations are discussed.